Profitability Moderates the Effect of Leverage, Liquidity, Activity, Operating Cash Flow, and Sales Growth on Financial Distress - Susmita Dian Indiraswari; Meisa Faiza Aulia; Ati Retna Sari (Department of Accounting, Faculty of Economics & Business, 2025)
This study aims to investigate the impact of leverage, liquidity, activity, operating cash flow, and sales growth on financial distress, as well as to examine whether profitability as a moderating variable can weaken or strengthen these effects. This quantitative study utilizes secondary data from 11 companies in the infrastructure, transportation, and logistics sectors that are listed on the Indonesia Stock Exchange from 2021 to 2023. This study uses Moderated Regression Analysis (MRA) with IBM SPSS Statistics version 25. The results indicate that leverage has a negative influence on financial distress, while liquidity has a positive impact. Additionally, activity has no significant effect, and operating cash flow and sales growth both have a negative impact on financial distress. Profitability is not effective in moderating the relationship between leverage, liquidity, and activity in terms of financial distress. Still, it can strengthen the negative effect of operating cash flow and sales growth on financial distress. This study implies that signaling theory is reinforced by the presence of high operating cash flows and consistent sales growth, which can signal a firm's ability to overcome financial distress. Building on this insight, this research aims to provide stakeholders with a foundation for informed decision-making and proactive corrective actions.